Touch of Chemokines - BLANCHET, Xavier; Langer, Marcella; Weber, Christian; Koenen, Rory R.; von Hundelshausen, Philipp (Frontiers in Immunology, 2012)
Chemoattractant cytokines or chemokines constitute a family of structurally related proteins found in vertebrates, bacteria or viruses. So far, 48 chemokines genes have been identified in humans, which bind to around 20 chemokine receptors. These receptors belong to the seven transmembrane G-protein-coupled receptors family. Chemokines and their receptors were originally studied for their role in cellular trafficking of leukocytes during inflammation and immune surveillance as well. It is now known that they exert different functions under physiological conditions such as homeostasis, development, tissue repair, and angiogenesis but also under pathological disorders including tumorigenesis, cancer metastasis, inflammatory and autoimmune diseases. Physicochemical properties of chemokines and chemokine receptors confer them the ability to homo- and hetero-oligomerize. Many efforts are currently performed in establishing new therapeutically compounds able to target the chemokine/chemokine receptors system. In this review, we are interested in the role of chemokines in inflammatory disease and leukocyte trafficking with a focus on vascular inflammatory diseases, the operating synergism and the emerging therapeutic approaches of chemokines.